Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

AFM-IR investigation of thin PECVD SiOx films on a polypropylene substrate in the surface-sensitive mode - Müller, Hendrik; Stadler, Hartmut; de los Arcos, Teresa; Keller, Adrian; Grundmeier, Guido (Beilstein Journal of Nanotechnology)
Thin silicon oxide films deposited on a polypropylene substrate by plasma-enhanced chemical vapor deposition were investigated using atomic force microscopy-based infrared (AFM-IR) nanospectroscopy in contact and surface-sensitive mode. The focus of this work is the comparison of the different measurement methods (i.e., contact mode and surface-sensitive mode) with respect to the chemical surface sensitivity. The use of the surface-sensitive mode in AFM-IR shows an enormous improvement for the analysis of thin films on the IR-active substrate. As a result, in this mode, the signal of the substrate material could be significantly reduced. Even layers that are so thin that they could hardly be measured in the contact mode can be analyzed with the surface-sensitive mode.

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

High-speed AFM studies of macromolecular dynamics at solid/liquid interfaces - Keller, Adrian; Grundmeier, Guido (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Cation-dependent assembly of hexagonal DNA origami lattices on SiO2 surfaces - Pothineni, Bhanu Kiran; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures have emerged as functional materials for applications in various areas of science and technology. In particular, the transfer of the DNA origami shape into inorganic materials using...
Keywords: General Materials Science

UV-enhanced environmental charge compensation in near ambient pressure XPS - Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Multiprotein Adsorption from Human Serum at Gold and Oxidized Iron Surfaces Studied by Atomic Force Microscopy and Polarization-Modulation Infrared Reflection Absorption Spectroscopy - Huang, Jingyuan; Qiu, Yunshu; Lücke, Felix; Su, Jiangling; Grundmeier, Guido; Keller, Adrian (Molecules)
Multiprotein adsorption from complex body fluids represents a highly important and complicated phenomenon in medicine. In this work, multiprotein adsorption from diluted human serum at gold and oxidized iron surfaces is investigated at different serum concentrations and pH values. Adsorption-induced changes in surface topography and the total amount of adsorbed proteins are quantified by atomic force microscopy (AFM) and polarization-modulation infrared reflection absorption spectroscopy (PM-IRRAS), respectively. For both surfaces, stronger protein adsorption is observed at pH 6 compared to pH 7 and pH 8. PM-IRRAS furthermore provides some qualitative insights into the pH-dependent alterations in the composition of the adsorbed multiprotein films. Changes in the amide II/amide I band area ratio and in particular side-chain IR absorption suggest that the increased adsorption at pH 6 is accompanied by a change in protein film composition. Presumably, this is mostly driven by the adsorption of human serum albumin, which at pH 6 adsorbs more readily and thereby replaces other proteins with lower surface affinities in the resulting multiprotein film.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Superstructure-dependent stability of DNA origami nanostructures in the presence of chaotropic denaturants - Hanke, Marcel; Dornbusch, Daniel; Tomm, Emilia; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (Nanoscale)
The structural stability of DNA origami nanostructures in various chemical environments is an important factor in numerous applications, ranging from biomedicine and biophysics to analytical chemistry and materials synthesis. In...
Keywords: General Materials Science

Thermophoretic Analysis of Biomolecules across the Nanoscales in Self-Assembled Polymeric Matrices - Liu, Ping; Schumann, Nils; Abele, Fabian; Ren, Fazheng; Hanke, Marcel; Xin, Yang; Hartmann, Andreas; Schlierf, Michael; Keller, Adrian; Lin, Weilin; Zhang, Yixin (ACS Applied Nano Materials)
Keywords: General Materials Science

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Genotype-phenotype mapping with polyominos made from DNA origami tiles - Dreher, Yannik; Fichtler, Julius; Karfusehr, Christoph; Jahnke, Kevin; Xin, Yang; Keller, Adrian; Göpfrich, Kerstin (Biophysical Journal)
Keywords: Biophysics

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos, Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al. (EMBO Molecular Medicine)
Keywords: Molecular Medicine

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian (Nanoscale)
The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading...
Keywords: General Materials Science

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Enhancement of the delamination resistance of adhesive film coated surface laser melted aluminum 7075-T6 alloy by aminophosphonic acid adsorption - Vieth, P.; Garthe, M.-A.; Voswinkel, Dietrich; Schaper, Mirko; Grundmeier, Guido (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Orive, Alejandro Gonzalez; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Electrografting of BTSE: Zn films for advanced steel-aluminum joining by plastic deformation - Duderija, B.; González-Orive, A.; Schmidt, H.C.; Calderón, J.C.; Hordych, I.; Maier, H.J.; Homberg, W.; Grundmeier, G. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Rieker, Florian; Meinderink, Dennis; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)